MLH1 function is context dependent in colorectal cancers. Issue 2 (17th December 2010) - Jackson, Thomas; Ahmed, Mohamed A H; Seth, Rashmi; Jackson, Darryl; Ilyas, Mohammad
Abstract : Background and aims: Loss of mismatch repair (MMR) function in sporadic colorectal cancer occurs most commonly because of inactivation of MLH1, and it causes an increase in mutation rate. However, it is uncertain whether loss of MMR alters any other cellular function. The aim of this study was to investigate the role of MMR in regulating cell numbers and apoptosis. Methods: MLH1 protein levels were manipulated by (a) cloning and forcibly expressing MLH1 in HCT116 (a cell line with MLH1 mutation) and RKO (a cell line with MLH1 silencing), and (b) knockdown of MLH1 in SW480 (a cell line with normal MMR function). Cell number and apoptotic bodies were measured in standard and 'high stress' (ie, after staurosporine exposure) conditions. Results: Restoration of MLH1 function in HCT116 and RKO resulted in increased cell number (p<0.001 for both cell lines) and decreased numbers of floating apoptotic bodies (p<0.01 in HCT116) in standard culture conditions. However, on induction of apoptotic stress, restoration of MLH1 resulted in reduced cell numbers (p<0.005). Knockdown of MLH1 in SW480 had no effect on cell numbers or apoptosis. Conclusions: MLH1 function may be context dependent: in 'low stress' conditions it may act to inhibit apoptosis, while in 'high stress' conditions it may induce apoptosis. However, within the context of chromosomal instability, the effect of MLH1 on cell numbers is limited.